Human flourishing in the context of farm characteristics and occupational hazards – Baseline findings from the FarmCoSwiss cohort (Swiss Medical Weekly, 2025)
INTRODUCTION AND OBJECTIVES: In Switzerland, little is known about farmers’ wellbeing. Based on cross-sectional baseline data from the Swiss agricultural health cohort FarmCoSwiss, we carried out a study to investigate farmers’ flourishing i.e. complete wellbeing and ability to thrive – to our knowledge, the first study worldwide to do so –, to descriptively compare it to the general population and to explore its association with farm characteristics and occupational hazards.METHODS: Of 1480 self-registered adult farmers recruited as a Swiss-wide convenience sample, 947 individuals (63.9%) signed the informed consent form, and 872 answered the online questionnaire in German, French or Italian at baseline between November 2022 and August 2023. The questionnaire obtained information on, among others, the primary outcome flourishing as assessed by the Secure Flourish Index (SFI) with its six subdomains Happiness and life satisfaction, Mental and physical health, Meaning and purpose, Character and virtue, Close social relationships, and Financial and material stability, each assessed on a scale from 0 to 10. Participants additionally answered questions on the primary predictors farm characteristics and 20 pre-selected occupational hazards classified into five domains (physical, chemical, biological, psychosocial and environmental). Participants assessed the hazards in terms of exposure frequency (Likert scale from 1 to 5) and perceived health harmfulness (Likert scale from 1 to 4). First, farmer’s mean SFI was descriptively compared to mean SFI in the general adult population using the data of 7220 participants from the 2023 follow-up of the population-based COVCO-Basel cohort established in Basel-Stadt and Basel-Landschaft cantons. Second, zero-one inflated beta regression models were constructed to investigate the age- and sex-adjusted association of mean SFI values (overall; domain-specific) with the farming system (non-organic or organic), the production system (animal husbandry or crop cultivation), farm size (five categories) as well as the exposure to, and perception of, occupational hazards (sum of respective Likert scales).RESULTS: Mean SFI values were between 7 and 8, in both FarmCoSwiss and COVCO-Basel. Descriptively comparing these two samples, farmers showed lower flourishing overall (7.44, SD = 1.41; COVCO: 7.70, SD = 1.30) and in the four domains Happiness and life satisfaction (7.39, SD = 1.87; COVCO: 7.91, SD = 1.55), Mental and physical health (7.03, SD = 1.73; COVCO: 7.68, SD = 1.53), Close social relationships (7.66, SD = 2.08; COVCO: 7.94, SD = 1.73) and Financial and material stability (7.06, SD = 2.45; COVCO: 7.33, SD = 2.69). Farmers reported being most frequently exposed to biological hazards (66.2% often/always exposed), but psychosocial hazards were perceived as the most harmful to health (51.9% judging them as rather/very harmful). Exposure to psychosocial hazards was negatively associated with overall flourishing and its six subdomains. In the domains Happiness and life satisfaction, Mental and physical health, and Meaning and purpose, organic farming was associated with higher flourishing. In the domain Close social relationships, organic farming was associated with lower flourishing. The largest association was observed for farm size. Farmers with the smallest farms (50 ha).CONCLUSION: Our findings suggest a potentially lower overall flourishing among farmers as compared to a sample from the general population, with small farm size and exposure to psychosocial hazards being of particular concern, but organic farming having potential benefits. The study underscores the need for longitudinal research of farmers’ wellbeing to maintain a thriving agricultural workforce.